TOPSIDE OPTIMIZATION METHODS FOR OFFSHORE PLATFORM MASS-SIZE CHARACTERISTICS. UTILIZING MODULAR DRILLING RIGS - Shestakov, Roman; Kamenskiy, Gleb; Rezanov, Konstantin; Zubkov, Stepan; Dryakhlov, Vyacheslav (Journal of Applied Engineering Science, 2024)
Offshore oil and gas production is associated with many times higher capital investments in development than onshore projects. In this regard, operators often give preference to less risky and less capital-intensive onshore projects. This, in turn, slows down the development of offshore production technologies and the development of the huge resource base of the Arctic shelf. Significant influence on the value of capital costs of offshore projects is the cost of offshore field development facilities, including the cost of offshore platforms - floating or stationary offshore oil and gas production structure consisting of topside and substructure, designed to accommodate drilling and/or production equipment, utilities equipment, systems and devices required to perform the functions assigned to the structure. One of the ways to reduce capital expenditures on platform construction is to reduce its weight and size, which can be achieved by using more modern compact technological equipment, improving design and construction technologies, as well as changing the platform concept itself. One of the key and largest functional units of topside offshore platform is the drilling complex. The possibility to quit the construction of the stationary drilling module and drill the well stock by alternative means, using jack-up or modular drilling rig, could become a growth driver for the economics of offshore construction projects. In this paper, a comparative analysis of alternative drilling methods and evaluation of economic efficiency of modular drilling rig application is carried out. As a result of the study, the following main conclusions were obtained: The analysis of statistical data has shown that the cost of topside structures linearly depends on the mass and dimensional characteristics, in which regard the optimization issues are highly important; The analysis of studies has shown the following: the studies do not offer a system of specific solutions to reduce the mass-dimensional characteristics of the upper structure of the offshore platform. The development of a solution for year-round drilling of the well stock on offshore platforms without the construction of a stationary drilling complex will significantly reduce the capital costs of development.